Uji Efikasi Beauveria Bassiana Untuk Pengendalian Hama Ulat Plutella Xylostella Pada Tanaman Kale (Brassica Oleracea) Var. Sabellica - Sutarman, Sutarman; Assholikhah, Aisyah Dirra; Prihatiningrum, Andriani Eko (Politeknik Negeri Lampung., 2023)
This study aimed to determine the effectiveness of Beauveria bassiana in controlling Plutella xylostella pests. The first stage of the experiment was conducted in vitro at the Pest and Disease Laboratory of UMSIDA by testing the ability of B. bassiana at spore densities of 100, 103, 105, and 107 CFU.mL-1 in inactivating P. xylostella caterpillars. The field application test was carried out on land endemic to leaf caterpillar pests in Seloliman Village, Mojokerto, East Java Province, Indonesia. The experiment was arranged in a Randomized Block Design with four B. bassiana spore density treatments repeated four times. Observations were made on the intensity of attack as well as wet weight and dry weight of plants. Data analysis used ANOVA followed by Duncan's test at the 5% test level to determine differences between treatments. The results showed that B. bassiana effectively deactivated the activity up to 60.2% in the application with a spore density of 107. The application of B. bassiana reduced the intensity of P. xylostella pest attack to 63.41% and increased the wet weight and dry weight of kale leaves by 246.0%. and 305.8% compared without B. bassiana application. The application of this entomopathogenic fungus can be a solution for controlling pests on land that is endemic to leaf caterpillar attacks